دراسة انتشار اضطراب التوحد في محافظتي (دمشق وريف دمشق) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
هدفت الدراسة الحالية إلى تحديد أعداد الأفراد المصابين باضطراب التوحد في محافظتي (دمشق، وريف دمشق) المقيدين في مراكز التربية الخاصة بالمعوقين (الحكومية، الأهلية) في العام الدراسي (2011-2012)، وتحديد (نسبة الذكور إلى الإناث) في هذه الإعاقة. وطبقت الدراسة على جميع مراكز التربية الخاصة في كلا المحافظتين والبالغ عددها (16) مركزاً منها (4 مراكز حكومية، 12 مركزاً أهلياً)، وبينت نتائج الدراسة فيما يتعلق بمحافظة دمشق أن أعداد (الذكور) المصابين باضطراب التوحد بلغ (146) حالة منهم (58 حالة من ذوي اضطراب التوحد بدون تخلف عقلي) بالإضافة إلى (88 حالة من ذوي اضطراب التوحد مع تخلف العقلي). أما أعداد (الإناث) المصابات باضطراب التوحد بلغ (108) منهن (52 حالة من ذوي اضطراب التوحد بدون تخلف عقلي) بالإضافة إلى (56 حالة من ذوي اضطراب التوحد مع تخلف عقلي). أما نسبة الذكور إلى الإناث فقد بلغت (1,32/1). وفي محافظة ريف دمشق بلغت أعداد (الذكور) المصابين باضطراب التوحد (440) حالة منهم (177 حالة من ذوي اضطراب التوحد بدون تخلف عقلي) بالإضافة إلى (263 حالة من ذوي اضطراب التوحد مع تخلف العقلي). أما أعداد (الإناث) المصابات باضطراب التوحد بلغ (307) منهن (112 حالة من ذوي اضطراب التوحد بدون تخلف عقلي) بالإضافة إلى (195 حالة من ذوي اضطراب التوحد مع تخلف عقلي). أما نسبة الذكور إلى الإناث فقد بلغت (1,67/1). وفي كلا المحافظتين (دمشق، ريف دمشق) بلغت أعداد (الذكور) المصابين باضطراب التوحد (586) حالة منهم (235 حالة من ذوي اضطراب التوحد بدون تخلف عقلي) بالإضافة إلى (351 حالة من ذوي اضطراب التوحد مع تخلف العقلي). أما أعداد (الإناث) المصابات باضطراب التوحد بلغ (415) منهن (164 حالة من ذوي اضطراب التوحد بدون تخلف عقلي) بالإضافة إلى (251 حالة من ذوي اضطراب التوحد مع تخلف عقلي). أما نسبة الذكور إلى الإناث فقد بلغت (1,41/1). كما عملت الدراسة على اقتراح نموذج لرعاية الأفراد المصابين باضطراب التوحد ضمن مراكز التربية الخاصة بالمعوقين في سورية وفق مجموعة خطوات كما يلي (التشخيص الدقيق والفارقي، تحديد أهداف البرامج التدريبية، تصميم البرامج التدريبية، تطبيق البرامج التدريبية، التحقق من فعالية البرامج التدريبية، الدمج)، كما توصلت الدراسة إلى مجموعة من المقترحات. The aim of the present study was to identify the number of autistic individuals in the governorates of (Damascus and Damascus Countryside) registered in special education centers of the handicapped (formal and community) during the school year (2011-2012). The study also aimed at defining the rate of males to females in this handicapped. The study was applied in all the special education centers in both governorates which amounted to (16) centers (4 formal centers and 12 community centers). In respect to Damascus governorate, the study findings showed that the number of autistic males was (146) cases, (58) cases of which were autistic individuals without mental retardation and (88) cases of which were autistic individuals with mental retardation. As for the females, the number of autistic females was (108) cases, (52) cases of which were autistic individuals without mental retardation and (56) cases of which were autistic individuals with mental retardation. The rate of males to females was (1.32/1). In relation to the governorate of Damascus Countryside, the study findings showed that the number of autistic males was (440) cases, (177) cases of which were autistic individuals without mental retardation and (263) cases of which were autistic individuals with mental retardation. As for the females, the number of autistic females was (307) cases, (112) cases of which were autistic individuals without mental retardation and (195) cases of which were autistic individuals with mental retardation. The rate of males to females was (1.67/1). In both governorates (Damascus and Damascus Countryside), the number of autistic males was (586) cases, (235) cases of which were autistic individuals without mental retardation and (351) cases of which were autistic individuals with mental retardation. As for the females, the number of autistic females was (415) cases, (164) cases of which were autistic individuals without mental retardation and (251) cases of which were autistic individuals with mental retardation. The rate of males to females was (1.41/1). In addition, the study aimed at suggestinga model to take care of autistic individuals within special education centers of the handicapped in Syria according to a set of steps as follows: (specific and distinctive diagnosis, identifying the program training goals, designing the training programs, applying the training programs, checking the effectiveness of the training programs, merging).The study reached at a set of suggestions.